Test-retest reliability of the FitMáx©-questionnaire in a clinical and healthy population - Renske Meijer; Goof Schep; Marta Regis; Nicole E. Papen-Botterhuis; Hans H. C. M. Savelberg; Martijn van Hooff (SpringerOpen, 2024)
Abstract Purpose The FitMáx© was developed as a questionnaire-based instrument to estimate Cardiorespiratory Fitness (CRF) expressed as oxygen uptake at peak exercise (VO2peak). Test-retest reliability is a clinometric measurement property, which defines stability over time if multiple measurements are performed (i.e. reliability). The present study aimed to assess the test-retest reliability of the FitMáx©-questionnaire in different patient groups. Patients and methods A total of 127 cardiac, pulmonary and oncology patients and healthy subjects aged 19-84 years who completed the questionnaire twice within an average of 18 days were included for analysis. Participants were in a stable clinical situation (no acute disease or participating in a training program). To determine the test-retest reliability, the Intraclass Correlation Coefficient (ICC) and Standard Error of the Measurement (SEM) was calculated between the first (T0) and second (T1) administration of the questionnaires. Results An excellent agreement was found between the FitMáx©-questionnaire scores at T0 and T1, with an ICC of 0.97 (SEM 1.91) in the total study population and an ICC ranging from 0.93 to 0.98 (SEM 1.52-2.27) in the individual patient groups. Conclusion The FitMáx©-questionnaire proves to be reliable and stable over time to estimate CRF of patients and healthy subjects. Trial registration NTR (Netherlands Trial Register), NL8846. Registered 25 August 2020, https://trialsearch.who.int/Trial2.aspx?TrialID=NL8846